2010
DOI: 10.1111/j.1651-2227.2010.01709.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the CART gene in overweight and obese Italian children using family‐based association methods

Abstract: Our results supported the hypothesis that inherited variations of the CART gene could influence the development of obesity also in Italian children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…It has been identified that CART prepropeptide gene polymorphism is associated with obesity [14]. Also Rigoli et al [15] declared that CART gene single nucleotide polymorphism (SNP) may affect CART expression which is associated with obesity in children. Other study by del-Giudice et al [16] suggested the possible role of Leu34Phe mutation of CART gene might play an important role in obese phenotype by altering the CART mediated leptin effect on thermogenesis and energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…It has been identified that CART prepropeptide gene polymorphism is associated with obesity [14]. Also Rigoli et al [15] declared that CART gene single nucleotide polymorphism (SNP) may affect CART expression which is associated with obesity in children. Other study by del-Giudice et al [16] suggested the possible role of Leu34Phe mutation of CART gene might play an important role in obese phenotype by altering the CART mediated leptin effect on thermogenesis and energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…The family-based association studies could examine associations within family groups, and so are robust to deal with population stratification, which is a known confounder of case–control studies [18]. Besides of the original qualitative TDT procedure, different methods and software packages have been designed for quantitative variables [1922], and have been used to provide more credible evidence in terms of genetic polymorphisms and phenotypes [2325]. …”
Section: Introductionmentioning
confidence: 99%
“…It is likely that c.517A→G is in LD with a functional casual polymorphism. There are currently very limited data on the role of CART polymorphisms (Leu 34 Phe, 1475A→G, –156T→C and –3608T→C) in the development of obesity [30,31,32,33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…Although the POMC gene is known to cause early-onset obesity accompanied by adrenal insufficiency and red hair pigmentation [27,28,29], together with CART , little is known about the role of these genes in polygenic obesity. To date, only four polymorphisms (Leu 34 Phe, 1475A→G, –156T→C and –3608T→C) in CART have been associated with obesity [30,31,32,33,34]. Many studies have focused on investigating the role of the leptin-melanocortin pathway and other associated proteins due to its central role in the regulation of energy intake and expenditure.…”
Section: Introductionmentioning
confidence: 99%